2018
DOI: 10.1016/j.ctro.2018.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of pseudoprogression after proton or photon therapy of 99 patients with low grade and anaplastic glioma

Abstract: HighlightsNo difference in pseudoprogression rate six months after proton or photon therapy.Oligodendrogliomas develop pseudoprogression sooner after protons vs. photons.Astrocytomas develop pseudoprogression at similar time after protons vs. photons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…After the removal of 214 duplicate articles, the title and abstract of the remaining 300 articles were evaluated against the selection criteria. Full-text analysis was performed for 18 articles, in which 9 retrospective observational cohort studies were assessed to satisfy all selection criteria for quantitative analysis, 5 studies [26][27][28][29][30] describing outcomes of pediatric LGG, and another 4 studies [15,[31][32][33] describing outcomes of adult LGG ( Table 1). Definitions of PsP by each study are included in Table 2.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of 214 duplicate articles, the title and abstract of the remaining 300 articles were evaluated against the selection criteria. Full-text analysis was performed for 18 articles, in which 9 retrospective observational cohort studies were assessed to satisfy all selection criteria for quantitative analysis, 5 studies [26][27][28][29][30] describing outcomes of pediatric LGG, and another 4 studies [15,[31][32][33] describing outcomes of adult LGG ( Table 1). Definitions of PsP by each study are included in Table 2.…”
Section: Search Strategymentioning
confidence: 99%
“…The 4 adult LGG studies [15,[31][32][33] described the PsP outcomes of 424 subjects, where 271 (64%) were treated with IMRT, and 153 (36%) were treated with PBT (Table 1). Median age ranged from 37 to 45 years old with proportion of female subjects ranging from 30% to 53% and median follow-up ranging from 0.5 to 6 years.…”
Section: Demographics and Clinical Features In The Adult Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoprogression can also be caused by proton therapy. A recent study among high‐grade gliomas showed similar incidences of pseudoprogression between conventionally irradiated patients and patients receiving proton therapy . However, little is known about pseudoprogression and the role of perfusion MRI for treatment follow‐up in GBM patients treated with proton beam therapy.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Numerous in vitro radiobiological studies for various cells using protons and photons have been carried out resulting in controversial data [21]. Authors showed that results are strongly influenced by the type of cells, culture condition, dose, dose rate, fractionation, and other physical features (i.e., LET, RBE) [22].…”
Section: Resultsmentioning
confidence: 99%